Арт-терапия (исцеление творчеством) и творческие ресурсы личности - Гончаров, Д. А. (ХНУРЕ, 2019)
The given work is devoted to study influence ot psyctioiogical state of a person on the creative potential. The results of people's creatity are studied in terms of art-therapy. Some problems connected with mixing different psychological methods with art-therapy are also reviewed in this article.